Orientasi Supervisi Pendidikan: Pendekatan, Kriteria, dan Peran Pengembangan dalam Meningkatkan Kualitas Pengajaran - Syaikhu, Muhammad; Qomariyah, Eva; Endang, Thesa Falahiyah; Deski, Melin Andini (Sunan Kalijaga International Journal on Islamic Educational Research, 2024)
In the increasingly competitive era of globalization, the role of teachers in education is becoming increasingly crucial, especially in shaping character and improving the quality of education. Educational supervision, conducted by school principals or competent parties, aims to improve the teaching and learning process, create a conducive learning environment, and avoid setbacks in the quality of education. This article discusses the importance of supervision in education, the types of supervision, and the criteria and orientation of effective supervision. Using the literature study method, this article provides an in-depth understanding of the role of supervision in improving the quality of education through various approaches tailored to the needs of teachers and educational institutions. The results of the literature analysis show that supervision does not only function as supervision, but also as guidance that encourages the development of individuals and educational institutions as a whole.